Formulation of Indigofera sp. Leaf Extract Nanoparticles Using Ionic Gelation and Freeze-Drying Method as a Feed Supplement for KUB Chickens: Improving Physicochemical Properties and Feed Applicability of Indigofera Extract - Akbar, Syahro A.; Astuti, Tri; Yunika , Putri; Adinda, Zulaikha (Universitas Veteran Bangun Nusantara, 2026)
This study aimed to formulate nanoparticles of ethanol extract of Indigofera sp. leaves using the ionic gelation method combined with freeze-drying, and to evaluate their potential as a feed supplement for Kampung Unggul Balitbangtan (KUB) chickens. Indigofera leaves are known to be rich in bioactive compounds, particularly tannins and flavonoids, which act as natural antioxidants that can enhance poultry growth performance and health. However, their limited stability and bioavailability reduce their effectiveness when directly applied in the diet. The encapsulation process was carried out with two treatments: P1 = without sonication and centrifugation, and P2 = with sonication but without centrifugation. The best results were obtained with sonication and without centrifugation, which produced a fine powder without clumping.